2016
DOI: 10.3892/mco.2016.1086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bevacizumab therapy for unresectable malignant glioma: A retrospective analysis

Abstract: Abstract. Bevacizumab (BEV), an inhibitor of vascular endothelial growth factor A, has been used for primary and recurrent malignant gliomas in Japan since June, 2013. Previous randomized controlled studies demonstrated that BEV prolonged the progression-free survival, but not the overall survival (OS) of patients with newly diagnosed glioblastoma. The aim of the present study was to elucidate the effect of BEV on the OS of patients with unresectable malignant gliomas. Of the 440 cases of malignant glioma init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In contrast, significantly more patients within the intention-to-treat (ITT) population treated with BEV (299/465, 64.3%) completed all six cycles of TMZ, while only 165 of 446 in the placebo group did (37%, p < 0.0001), consistent with the shorter PFS in the placebo pus TMZ group. In contrast, Yonezawa and colleagues 34 reported a single-centre retrospective analysis of 88 cases with HGG, who over time received different primary adjuvant treatments, lomustine/procarbazine/vincristine from 2000 to 2006, TMZ from 2006 to 2013 and TMZ plus BEV from 2013 to 2016. Improvements in neurosurgical techniques were excluded as a confounder by choosing cases that received biopsies only.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, significantly more patients within the intention-to-treat (ITT) population treated with BEV (299/465, 64.3%) completed all six cycles of TMZ, while only 165 of 446 in the placebo group did (37%, p < 0.0001), consistent with the shorter PFS in the placebo pus TMZ group. In contrast, Yonezawa and colleagues 34 reported a single-centre retrospective analysis of 88 cases with HGG, who over time received different primary adjuvant treatments, lomustine/procarbazine/vincristine from 2000 to 2006, TMZ from 2006 to 2013 and TMZ plus BEV from 2013 to 2016. Improvements in neurosurgical techniques were excluded as a confounder by choosing cases that received biopsies only.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…A Cox proportional hazard model analysis led to BEV in addition with lower tumour grade and higher functional status as main predictor of prolonged survival. 34 In addition, a large retrospective study comprising 28.933 GB patients in the US prior TMZ approval, after TMZ approval and prior BEV approval for recurrent GB and after BEV approval showed an increasing OS over time due to administration of firstly TMZ concomitant with radiotherapy and adjuvant afterwards for newly diagnosed GB and then secondly due to the administration of BEV for recurrent GB. 35 …”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Accordingly, real-world data from retrospective studies conducted by Japanese institutions appear promising in providing evidence of first-line BEV efficacy for patients with severe clinical conditions. Yonezawa et al [ 27 ] retrospectively analyzed newly diagnosed malignant glioma and reported that the use of BEV is an independent beneficial factor associated with prolonged OS in patients with unresectable GBM [BEV vs. non-BEV median OS: 566 vs. 160 days, HR 0.25 (0.10–0.65), p = 0.001]. We previously demonstrated that first-line BEV prevents deterioration during concurrent TMZ treatment and radiotherapy, and contributes to OS prolongation in patients with unresectable tumors (BEV vs. without BEV median OS: 17.4 vs. 9.8 months, p = 0.075) [ 28 ]; this highlights the advantages of first-line BEV for severe clinical conditions such as unresectable tumors and poor PS ( p = 0.017).…”
Section: First-line Bevmentioning
confidence: 99%
“…A possible reason for the failure of BEV to improve OS despite its prolongation of PFS in clinical trials is that BEV treatment may show changes in imaging findings that are not necessarily correlated with beneficial effects on tumor biology [ 30 ]. However, recent real-world data from Japanese institutes, in which BEV is available as a first-line treatment, indicate improved survival with selective administration of first-line BEV combined with TMZ for patients with severe clinical conditions such as unresectable cases or poor PS [ 27 , 28 , 29 , 31 ]. Nevertheless, the evidence level is not sufficiently high as these reports are institutional and retrospective studies, and BEV usage is institution-specific.…”
Section: First-line Bevmentioning
confidence: 99%
“…Despite maximal therapy including surgical resection, average survival is only 20 months [ 2 ]. Some patients are not candidates for surgery due to poor health, deep or bilateral location or proximity to eloquent structures [ 3 , 4 ]. Without cytoreductive surgery, the average survival is four months [ 2 ].…”
Section: Introductionmentioning
confidence: 99%